Efektivitas LKPD IPA Terpadu Tema Energi dalam Kehidupan Dengan PBL Terintegrasi Pembelajaran Abad 21 untuk Meningkatkan Sikap Peserta Didik - Gusti, Dian Arima; Ratnawulan, Ratnawulan (Universitas Negeri Padang, 2021)
The curriculum is very important factor in the world of education. In order for the success of the 2013 curriculum in the learning process to run well, it is necessary to implement the use of the 2013 curriculum. In this case, student worksheets are selected as sources and teaching materials that will be used in the learning process. Based on the preliminary analysis, most of the outstanding student worksheets contain a summary of the material that is not attractive and also has not used the right model and has not been integrated in 21st century learning. In addition, integrated science using student worksheets in the 2013 curriculum is also packaged in an integrated manner on character building through character education. For this reason, the purpose of this research is to see the effectiveness of student worksheets in integrated science learning using integrated PBL in 21st century learning which is reviewed in the attitude competency aspects of students. The research was conducted in class VII.4 Junior High School of 4 Pasaman. The data used in this study were primary data, namely data obtained through a questionnaire, while the character assessment instrument consisted of self-assessment sheets which were carried out using assessment sheets. Based on the results of the research, it can be concluded that the integrated student worksheets with the theme of energy in daily life using integrated PBL 21st century learning has been effectively used by students in the learning process to achieve the attitudinal competence.